Implementasi Strategi Writing to Learn untuk Meningkatkan Kemampuan Kognitif dan Keterampilan Berpikir Kritis Siswa SMA pada Materi Hukum Newton - Hilda Nurul Melida; Parlindungan Sinaga; Selly Feranie (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Abstract The result of former study showed that students’ cognitive ability and critical thinking skills were still low. The ‘writing to learn’ strategy is predicted to be able to enhance students’ cognitive ability and critical thinking skills. The aims of this research are (1) investigate the comparison of cognitive ability and critical thinking skills enhancement between the classes that apply the use of ‘writing to learn’ strategy and the classes that administer conventional learning, (2) examine the effectiveness of ‘writing to learn’ strategy in improving cognitive ability and critical thinking skills, and (3) examine the relationship between the quality of writing and cognitive ability and critical thinking skills. This research used nonequivalent control group design in high school one of Bandung. The result showed the implementation of ‘writing to learn’ strategy increased students’ cognitive ability and critical thinking skills of newtons’ laws of motion in experiment class, i.e. with each value of n-gain was 0.58 and 0.67 that the increase was higher than the control class, i.e. with each value of n-gain was 0.36 and 0.50. ‘Writing to learn’ strategy gave an impact towards the enhancement of students’ cognitive ability and critical thinking skills with each value of the effect size was 0.80 and 1.1. The quality of writing gave enough contribution in improving cognitive ability and critical thinking skills with each coefficient of correlation 0.24 and 0.63. Keywords : Writing to learn strategy, cognitive ability, critical thinking skills. Abstrak Hasil studi pendahuluan memperlihatkan bahwa siswa memiliki kemampuan kognitif dan keterampilan berpikir kritis yang masih rendah. Strategi writing to learn diprediksi dapat meningkatkan kemampuan dan keterampilan berpikir kritis siswa. Penelitian ini bertujuan untuk (1) mengetahui perbandingan peningkatan kemampuan kognitif dan keterampilan berpikir kritis antara kelas yang menggunakan strategi writing to learn dengan kelas yang melaksanakan pembelajaran konvensional, (2) mengetahui keefektifan strategi writing to learn dalam meningkatkan kemampuan kognitif dan keterampilan berpikir kritis, serta (3) mendapat gambaran mengenai hubungan antara kualitas menulis dengan kemampuan kognitif dan keterampilan berpikir kritis. Penelitian ini menggunakan desain nonequivalent control group design di salah satu SMA Negeri di kota Bandung. Hasil penelitian menunjukkan adanya pengaruh dari implementasi strategi writing to learn dalam meningkatan kemampuan kognitif dan keterampilan berpikir kritis pada materi hukum Newton di kelas eksperimen, yaitu dengan masing-masing nilai n-gain sebesar 0,58 dan 0,67 yang lebih besar peningkatannya dibandingkan dengan kelas kontrol, yaitu dengan masing-masing nilai n-gain sebesar 0,36 dan 0,50. Strategi writing to learn berdampak pada peningkatkan kemampuan kognitif dan keterampilan berpikir kritis siswa dengan masing-masing nilai effect size yaitu 0,80 dan 1,1. Kualitas menulis cukup berkontribusi dalam meningkatkan kemampuan kognitif dan keterampilan berpikir kritis dengan masing-masing koefisien korelasi 0,63 dan 0,24. Kata-kata kunci : Strategi writing to learn, kemampuan kognitif, keterampilan berpikir kritis.